Mastering Visual C# .NET - Price, Jason (Sybex, 2002)
Mastering Visual C# .NET is the best resource for getting everything you can out of the new C# language and the .NET Framework. You'll master C# language essentials, quickly taking advantage of the many improvements it offers over C++ and see tons of examples that show you all the ways that .NET can make your programming more efficient and your applications more powerful. You'll learn how to create stand-alone applications, as well as build Windows, web, and database applications. You'll even see how to develop web services--a technology that holds great promise for the future of distributed application.